2018
DOI: 10.1515/sjecr-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between the Immunohistochemical Expression of P53 and the Proliferation Index in the Keratinocyte Tumors of the Skin

Abstract: P53 is important for cell cycle regulation, and its overexpression is seen in malignant tumors. We examined correlation between p53 expression and cell proliferation, and its role in the pathogenesis of keratinocyte skin tumors. We used biopsies from patients with squamous cell carcinoma, actinic keratosis and keratoacanthoma. We examined crosssections stained with HE and using anti-cytokeratin, antip53 and anti-Ki67 antibodies. Expression of p53 is found in 87, 85% of SCC, in 83. 3% of AK and 13. 4% KA. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Some authors believe that p53 expression is related to sun exposure and increased age in the cases of AK. 22,23 The expression of p53 also decreased in regressed AK and non-sun-exposed skin compared with sun-exposed skin and clinically apparent AK. 24 Ishida et al and our findings demonstrated that p53 stained basal keratinocytes in AK and left them unstained in BD.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Some authors believe that p53 expression is related to sun exposure and increased age in the cases of AK. 22,23 The expression of p53 also decreased in regressed AK and non-sun-exposed skin compared with sun-exposed skin and clinically apparent AK. 24 Ishida et al and our findings demonstrated that p53 stained basal keratinocytes in AK and left them unstained in BD.…”
Section: Discussionmentioning
confidence: 93%
“…This may demonstrate that another pathway may participate in tumorigenesis. Some authors believe that p53 expression is related to sun exposure and increased age in the cases of AK 22,23 . The expression of p53 also decreased in regressed AK and non‐sun‐exposed skin compared with sun‐exposed skin and clinically apparent AK 24 .…”
Section: Discussionmentioning
confidence: 99%